Mesenchymal Stem Cells and Three-Dimensional-Osteoconductive Scaffold Regenerate Calvarial Bone in Critical Size Defects in Swine. (1st April 2021) - Johnson, Zoe M.; Yuan, Yuan; Li, Xiangjia; Jashashvili, Tea; Jamieson, Michael; Urata, Mark; Chen, Yong; Chai, Yang
Abstract: Craniofacial bones protect vital organs, perform important physiological functions, and shape facial identity. Critical-size defects (CSDs) in calvarial bones, which will not heal spontaneously, are caused by trauma, congenital defects, or tumor resections. They pose a great challenge for patients and physicians, and significantly compromise quality of life. Currently, calvarial CSDs are treated either by allogenic or autologous grafts, metal or other synthetic plates that are associated with considerable complications. While previous studies have explored tissue regeneration for calvarial defects, most have been done in small animal models with limited translational value. Here we define a swine calvarial CSD model and show a novel approach to regenerate high-quality bone in these defects by combining mesenchymal stem cells (MSCs) with a three-dimensional (3D)-printed osteoconductive HA/TCP scaffold. Specifically, we have compared the performance of dental pulp neural crest MSCs (DPNCCs) to bone marrow aspirate (BMA) combined with a 3D-printed HA/TCP scaffold to regenerate bone in a calvarial CSD (>7.0 cm 2 ). Both DPNCCs and BMA loaded onto the 3D-printed osteoconductive scaffold support the regeneration of calvarial bone with density, compression strength, and trabecular structures similar to native bone. Our study demonstrates a novel application of an original scaffold design combined with DPNCCs or BMA to support regeneration of high-quality bone in a newly defined and clinically relevant swine calvarial CSD model. This discovery may have important impact on bone regeneration beyond the craniofacial region and will ultimately benefit patients who suffer from debilitating CSDs. Abstract : In this study, we define a swine calvarial critical-sized defect (CSD) model and show a novel approach to regenerate high-quality bone in these defects. We compare the performance of dental pulp neural crest mesenchymal stem cells to bone marrow aspirate combined with an innovative three-dimensional-printed hydroxyapatite tricalcium phosphate scaffold to regenerate bone in a calvarial CSD (>7.0 cm 2 ). Courtesy of Sarah Pyle.